The Early History of Program Evaluation and the U.S. Department of Labor - Orley C. Ashenfelter (Institute for the Study of Labor (IZA), 2014)
This paper contains a review of the early history of program evaluation research at the US Department of Labor. Some broad lessons for successful evaluation research are summarized.
Keywords: B4; C21; J8; 330; program evaluation; training programs; active labor market programs